2015
DOI: 10.3920/wmj2014.1758
|View full text |Cite
|
Sign up to set email alerts
|

Lack of aflatoxin production byAspergillus flavus is associated with reduced fungal growth and delayed expression of aflatoxin pathway genes

Abstract: Aflatoxins, produced by Aspergillus flavus and Aspergillus parasiticus, are the most toxic fungal secondary metabolites that contaminate agricultural commodities such as peanuts, cotton and maize. Understanding the underlying mechanisms of crop resistance to fungal infection is an important step for plant breeders to develop better and improved crop varieties for safe production of human food and animal feed. Infection studies have identified a resistant (R) peanut line, GT-C20, which is able to decrease aflat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Although our in vitro data is consistent with field studies in regard to aflatoxin resistance of ICG 1471, additional field and laboratory studies are needed to define the resistance mechanisms for this genotype. GT-C20 was previously reported to limit A. flavus fungal growth and inhibit aflatoxin production [ 33 ], which is contrary to our findings. Both our field and in vitro studies demonstrated the high susceptibility of GT-C20 to A. flavus fungal growth and aflatoxin production.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Although our in vitro data is consistent with field studies in regard to aflatoxin resistance of ICG 1471, additional field and laboratory studies are needed to define the resistance mechanisms for this genotype. GT-C20 was previously reported to limit A. flavus fungal growth and inhibit aflatoxin production [ 33 ], which is contrary to our findings. Both our field and in vitro studies demonstrated the high susceptibility of GT-C20 to A. flavus fungal growth and aflatoxin production.…”
Section: Resultscontrasting
confidence: 99%
“…ICG 1471 also is drought tolerant [ 31 ]. GT-C20 is a Chinese cultivar [ 32 ] reported to retard A. flavus fungal growth and prevent aflatoxin production [ 33 ]. C76-16 is a drought tolerant USDA breeding line with field aflatoxin resistance [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two cultivated peanuts, including GT-C20 and Tifrunner, were obtained from Shandong Center of Crop Germplasm Resources, Jinan, China, and the voucher specimens were deposited in the Shandong Center of Crop Germplasm Resources. The resistance of GT-C20 and Tifrunner to A. flavus has ever been reported in previous studies [76]. The A. flavus strain (AF-Wh2014) isolated from peanut was kindly provided by lab of Prof. Boshou Liao, Oil Crops Research Institute of Chinese Academy of Agricultural Sciences.…”
Section: Plant Materials and Treatment Conditionmentioning
confidence: 79%